2003
DOI: 10.1063/1.1625639
|View full text |Cite
|
Sign up to set email alerts
|

Formation of neutral and charged gold carbonyls on highly facetted gold nanostructures

Abstract: We show that gold mono- and di-carbonyls are formed on gold field emitter tips during interaction with carbon monoxide gas at room temperature and in the presence of high electrostatic fields. The experiments are done in a time-of-flight atom probe to obtain mass spectra. The yield of monocarbonyl cations is about twice that of di-carbonyl ions. Density functional theory calculations are reported that explain the field stabilization of adsorbed carbonyls and the desorption yield of their cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…In a previous PFDMS study of CO adsorption on Au [9] we have demonstrated the formation of AuCO and Au(CO) 2 singly or doubly charged ions suggesting CO twin bound at steps. The intensities of these species was found to depend strongly on the steady field strength applied between pulses and the data could be quantitatively assessed by DFT calculations.…”
Section: Resultsmentioning
confidence: 95%
“…In a previous PFDMS study of CO adsorption on Au [9] we have demonstrated the formation of AuCO and Au(CO) 2 singly or doubly charged ions suggesting CO twin bound at steps. The intensities of these species was found to depend strongly on the steady field strength applied between pulses and the data could be quantitatively assessed by DFT calculations.…”
Section: Resultsmentioning
confidence: 95%
“…13 These calculations were performed along with an experimental study with PFDMS, which aimed at establishing relationships between the existence of gold carbonyl complexes and the static field strength on the tip. As in the case of oxygen, gold carbonyl formation is promoted by the presence of partial positive charges associated with a static (positive) electric field.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of the wave occurs close to the central pole, where the field is the highest, and then propagates away from the nucleation region down to the shank of the tip [201]. It has been shown that the application of an external field induces the presence of gold-carbonyls [199] but does not induce the adsorption/dissociation of oxygen species [200]. It is thus rather unlikely that the propagation wave corresponds to CO oxidation.…”
Section: Processes On Au Tips Propagation Waves During Co/o 2 Interacmentioning
confidence: 99%
“…The study of CO adsorption on Au tips [199] suggests the formation of gold mono-and di-carbonyls, as shown in Figure 13b representing the mass spectra obtained during CO adsorption at room temperature. Gold carbonyls are indeed observed, in the presence of high electrostatic field, as AuCO + , AuCO 2+ and Au(CO) 2 + species.…”
Section: Processes On Au Tips Propagation Waves During Co/o 2 Interacmentioning
confidence: 99%
See 1 more Smart Citation